Use of a negative binomial distribution to describe the presence of Sphyrion laevigatum in Genypterus blacodes - Peña-Rehbein,Patricio (2013)
This paper describes the frequency and number of Sphyrion laevigatum in the skin of Genypterus blacodes, an important economic resource in Chile. The analysis of a spatial distribution model indicated that the parasites tended to cluster. Variations in the number of parasites per host could be described by a negative binomial distribution. The maximum number of parasites observed per host was two.